My very first Mother Goose - Opie, Iona Archibald; Wells, Rosemary (Candlewick Press, 1996)
A collection of more than sixty nursery rhymes including "Hey Diddle, Diddle," "Pat-a-Cake," "Little Jack Horner," and "Pussycat, Pussycat."